Persepsi Generasi Z terhadap Wisata Edukasi Berbasis 7Ws di Desa Wisata Letvuan Paradise Kepulauan Kei - Rahmat Abdullah; Anggraeni M.S Lagalo; Yulin Panigoro (Tulisan Ilmiah Pariwisata (TULIP), 2026)
Tourism development has recently shifted from single-attraction-based recreation toward experience-based tourism that emphasizes learning, authenticity, and tourist engagement. This study aims to examine Gen Z students’ perceptions of educational tourism in Letvuan Paradise Tourism Village, Kei Islands, using the 7Ws framework, namely what to see, what to do, what to buy, what to arrive, what to stay, what to learn, and what the service. This study employed a quantitative approach involving a sample of 145 Gen Z students from the Marine Agrotourism Study Program at Tual State Fisheries Polytechnic who had participated in a study tour. Data were collected using a four-point Likert scale questionnaire and were analyzed descriptively through frequency distribution and mean scores. The results show that students’ perceptions of Letvuan Paradise Tourism Village were generally positive, particularly regarding natural, cultural, historical, and culinary attractions, accessibility, accommodation, services, and learning aspects. However, the educational experience was still dominated by visual and narrative activities, while direct involvement in seaweed production, local culinary processing, and community life remained limited. This study concludes that Letvuan Paradise needs to design and implement educational tourism packages that are interactive, authentic, affordable, and based on local practices.